Transhumanity, Posthumanity, Anthropocene: Shifting Horizons of Ignorance and Knowledge, Reality and Possibility, Hope and Faith - Cormie, Lee ca. 21. Jh. (Concilium, 2021)
The whole of Creation is in turmoil, and so are our ways of knowing the world and acting in it. Here I highlight three powerful new discourses of transhumanism, posthumanism, and Anthropocene, for insights into the magnitude of the epochal transitions underway on Planet Earth, increasingly God-like human capacities to act, inevitable leaps of hope and faith tipping the balance toward widely divergent possible futures.